Evaluation of insecticides for the control of serpentine leaf miner (Liriomyza trifolii Burgess) in castor: EVALUATION OF INSECTICIDES FOR THE CONTROL OF SERPENTINE LEAF MINER - V B AKASHE; M A GUD; S K SHINDE; V M TORADMAL; J R KADAM (Journal of Oilseeds Research, 2013)
Field experiments were conducted with seven treatments viz., Carbaryl 50 WP @ 0.2%, Endosulfan 35 EC @ 0.05%, Triazophos 40 EC @ 0.05%, Spinosad 45 SC @ 0.018%, Fipronil 5 SC @ 0.01%, Neem seed extract @ 5% (w/v) and untreated treatment for the control ofserpentine leaf miner (Liriomyza trifolii Burgess) on castor (Ricinus communis L.) cultivar DCS-9 during the rainy seasons of 2007, 2008 and 2010. Two sprays of all the treatments except untreated control were applied 30 and 45 days after sowing. The treatment with 0.018% Spinosad was the most effective in suppressing leaf miner infestation and resulted in to higher seed yield (803 kg/ha) followed by 0.05% spray of Triazophos (761 kg/ha). The economics of the treatments revealed the highest B:C ratio (1.98) by Triazophos 0.05% followed by Spinosad 0.018% (1.52), Carbaryl 0.2% (1.28), Endosulfan 0.05% (1.25) and Fipronil 0.01% (1.11). The other treatments were found relatively less effective for the control of leaf miner.